Rill Erosion in Unpaved and Rock-Paved Roads after Wildfire in a Mediterranean Forest - Manuel Esteban Lucas-Borja; Demetrio Antonio Zema (Geosciences, 2021)
Forest roads are often subject to intense runoff and erosion, and the rates can be increased by other disturbance factors, such as wildfires. Since scarce literature exists on the effects of wildfires on rill erosion of forest roads, this study presents the first results of a wider research, evaluating rill erosion in four different types of roads on a forest in Hellìn (Castilla-La Mancha, Central-Eastern Spain): unpaved roads made of native materials (soil found at the study site) and rock-paved roads, both built in unburned areas as well as unpaved and rock-paved roads, in fire-affected areas. In general, the unpaved roads are more subject to rill erosion compared to the rock-paved roads. In particular, the road of burned areas shows an erodibility that is higher by more than 200% compared to the unpaved and unburned roads, and even by about 400% compared to rock-paved roads (in both burned and unburned areas). A modeling approach based on distance linear models and distance-based redundancy analysis has identified the slope of road surface and upstream hillslope as well as the percent bare soil over the road surface as important input variables to predict rill erosion in future modeling experiences. All these variables may be easily measured by quick field surveys. Although the analytical approach of this study is limited to the geometric characteristics of erosion features, the results and the methods developed are useful to support the activity of land managers to better understand the magnitude of road erosion and to develop efficient measures for its control and mitigation.